2010
DOI: 10.1073/pnas.1000027107
|View full text |Cite
|
Sign up to set email alerts
|

In vivo expansion of naive and activated CD4 + CD25 + FOXP3 + regulatory T cell populations in interleukin-2–treated HIV patients

Abstract: HIV-1 infection is characterized by a progressive decline in CD4 + T cells leading to a state of profound immunodeficiency. IL-2 therapy has been shown to improve CD4 + counts beyond that observed with antiretroviral therapy. Recent phase III trials revealed that despite a sustained increase in CD4 + counts, IL-2-treated patients did not experience a better clinical outcome [Abrams D, et al. (2009) N Engl J Med 361(16):1548-1559. To explain these disappointing results, we have studied phenotypic, functional, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 39 publications
3
52
1
1
Order By: Relevance
“…On the other hand, excess Treg activity results in "over" suppression of immune responses resulting in too much immune suppression, leading to faster HIV progression and negative outcomes (Kinter, Horak et al, 2007). This point is also supported by a report showing that recombinant IL-2 treatment in a phase III trial actually enhanced Treg populations, possibly explaining why this treatment failed to elicit better clinical outcome (Weiss, Letimier et al, 2010). Treg depletion has been associated with an increase in immune activation (Eggena, Barugahare et al, 2005) and several important studies have demonstrated correlation of Treg proliferation and turnover with lower CD4 counts (Bi, Suzuki et al, 2009;Piconi, Trabattoni et al, 2010;Xing, Fu et al, 2010).…”
Section: Treg In Hiv Infectionsupporting
confidence: 61%
“…On the other hand, excess Treg activity results in "over" suppression of immune responses resulting in too much immune suppression, leading to faster HIV progression and negative outcomes (Kinter, Horak et al, 2007). This point is also supported by a report showing that recombinant IL-2 treatment in a phase III trial actually enhanced Treg populations, possibly explaining why this treatment failed to elicit better clinical outcome (Weiss, Letimier et al, 2010). Treg depletion has been associated with an increase in immune activation (Eggena, Barugahare et al, 2005) and several important studies have demonstrated correlation of Treg proliferation and turnover with lower CD4 counts (Bi, Suzuki et al, 2009;Piconi, Trabattoni et al, 2010;Xing, Fu et al, 2010).…”
Section: Treg In Hiv Infectionsupporting
confidence: 61%
“…Accordingly, IL-2 therapy in lymphopenic patients leads to increases in regulatory-like CD4 T cell counts at the expense of the conventional T cell compartment, leading to altered responses to pathogens (46)(47)(48). Conversely, administration of IL-7 in humans induces expansion of naive and memory T cell subsets (49)(50)(51) and, in some clinical trials, a relative decrease in the percentage of regulatory CD4 + T cells was observed (52).…”
Section: Regulatory Cd4 + T Cells Receive Help From Conventional Cd4 mentioning
confidence: 99%
“…Expanded Tregs suppressed proliferation of effector T cells in vitro, a result that may explain why these patients did not experience a clinical benefit despite sustained increases in CD4 counts. 59 In contrast to IL-2, recombinant IL-7 therapy was found to preferentially expand non-Treg cells resulting in a relative decrease of Treg within the total CD4 T-cell population. 60 The role of Treg should also be considered in therapeutic vaccine trials for HIV infection since Treg may prevent the vaccine-induced anti-HIV-1-specific polyfunctional responses.…”
Section: Treg Frequency Changes In Peripheral Bloodmentioning
confidence: 99%